Pelvic Chondrosarcoma Treated by En Bloc Resection with Patient-Specific Osteotomy Guides and Reimplantation of the Extracorporeally Irradiated Bone as an Osseocartilaginous Structural Orthotopic Autograft: A Report of Two Cases with Description of the Surgical Technique - Georgios Gkagkalis; Kevin Moerenhout; Hannes A. Rüdiger; Daniel A. Müller; Igor Letovanec; Stephane Cherix (Case Reports in Orthopedics)
Primary tumors of the pelvis are considered difficult to treat due to the complex anatomy and the proximity of important neurovascular structures. The surgical armamentarium for the treatment of these tumors has evolved with the help of cutting-edge technology from debilitating hemipelvectomies to solutions such as precise resections guided by patient-specific instruments or computer navigation and reconstruction by modular prostheses, 3D-printed custom-made implants, or orthotopic autograft reimplantation after extracorporeal irradiation. Different combinations of these techniques have been described in the literature with various rates of success. We present two cases of pelvic chondrosarcomas successfully treated by a combination of periacetabular resection with patient-specific osteotomy guides and orthotopic reimplantation of the extracorporeally irradiated autograft resulting in retention of the native hip.